The achievement gap in Indonesia? Organizational and ideological differences between private Islamic schools. Issue 2 (2nd April 2020) - Muttaqin, Tatang; Wittek, Rafael; Heyse, Liesbet; van Duijn, Marijtje
ABSTRACT: This study examines the effects of different types of private Islamic schools on student achievement and achievement gaps. We formulate hypotheses, drawing on an education production function approach that outlines differences in investment and resource allocation decisions across these tracks and streams. We tested our hypotheses using Indonesian data collected in 2013 on 156, 952 students nested in 3, 150 schools in 366 municipalities. Using multilevel regression analyses, we found that student achievement and achievement gaps vary over private Islamic school tracks and streams. Even though student achievement and achievement gaps are strongly determined by student and family characteristics, our findings suggest that differences between school tracks and streams also play an important role. Moreover, our study revealed a large variability in student achievement and achievement gaps between municipalities.